2015
DOI: 10.19030/jabr.v32i1.9483
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Crude Oil Prices And Economic Growth In Selected OPEC Countries

Abstract: <p>The aim of this study is to examine the degree of interdependence between oil prices and economic activity growth for four major countries (United Arab Emirates, Kuwait, Saudi Arabia, and Venezuela) in the Organization of the Petroleum Exporting Countries (OPEC) over the period from 3 September 2000 to 3 December 2010. We propose the frequency approach of Priestley and Tong (1973), which is the evolutionary co-spectral analysis. This method  offers a time-varying dynamic correlation measure for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 20 publications
6
52
0
1
Order By: Relevance
“…Increase in oil prices will lower output, which lowers real wages due to the decline in demand for labor as a result of the decline in economic growth. A decline in economic growth is positively linked with less disposable income and consumption as well (Maeda 2008, Tang et al 2010, Ftiti et al 2016). …”
Section: The Model and Datamentioning
confidence: 99%
“…Increase in oil prices will lower output, which lowers real wages due to the decline in demand for labor as a result of the decline in economic growth. A decline in economic growth is positively linked with less disposable income and consumption as well (Maeda 2008, Tang et al 2010, Ftiti et al 2016). …”
Section: The Model and Datamentioning
confidence: 99%
“…However, the oil price shocks create undermine and uncertainty effective fiscal management of oil revenues. Ftiti et al (2016) the researcher studied the degree of interdependence between oil price shocks and economic growth for (United Arab Emirates, Kuwait, Saudi Arabia, and Venezuela) in OPEC during the period from 2000 to 2010. They used co-integration test, the researcher showed that oil price shock short-term and medium-term during the period of fluctuations in financial turmoil and the global business cycle impact on economic growth in Organization of the Petroleum Exporting Countries.…”
Section: Research Conductedmentioning
confidence: 99%
“…It aligns with the result in Rahma et al (2016). However, it contradicts Oriakhi and Iyoha (2013) who suggest a positive link between oil price volatility and deficit financing of its associated high government expenditure and Hamilton (1983) and Ftiti, Guesmi, Teulon, and Chouachi (2016) which show that high oil price lowers national income and thereby raises fiscal deficit. Note: *, **, *** 1%, 5%, 10% significance level.…”
Section: Ardl Regression Resultsmentioning
confidence: 75%